Neurogenic pulmonary oedema as a rare complication of epileptic seizures - Sova, Milan; Franc, David; Ctvrtlik, Filip; Jakubec, Petr; Ghazal Asswad, Amjad; Kolek, Vitezslav (Advances in respiratory medicine, 2019)
INTRODUCTION: Neurogenic pulmonary oedema (NPE) is avery rare complication of epileptic seizures, which could potentially increase mortality. MATERIAL AND METHODS: The case of a66-year-old male patient with NPE caused by repeated epileptic seizures is reported. Rapid resolution of pulmonary oedema is well documented by X-ray and computed tomography images. CONCLUSIONS: Neurogenic pulmonary oedema could potentially increase mortality, and thus, it is important to perform achest X-ray in all patients presenting with seizures and dyspnoea.
Keywords: mužské pohlaví; Pulmonary Edema; epilepsy; senioři; nemoci centrálního nervového systému; Male; Central Nervous System Diseases; lidé; Central Nervous System; Humans; hemodynamika; neurogenic pulmonary oedema; seizure; Aged; centrální nervový systém; Hemodynamics; plicní edém